2020
DOI: 10.2147/idr.s244990
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of the Antimicrobial and Antibiofilm Effect of Chitosan Nanoparticles as Carrier for Supernatant of Mesenchymal Stem Cells on Multidrug-Resistant <em>Vibrio cholerae</em></p>

Abstract: Aim The aim of the present study was to evaluate the in vitro antimicrobial and antibiofilm activity of chitosan nanoparticles (CS NPs) incorporated with mesenchymal stem cells-derived conditioned media (MSCs CM) on MDR Vibrio cholerae strains. Materials and Methods Chitosan NPs were prepared and characterized by dynamic light scattering (DLS), scanning electron microscope (SEM) and zeta potential measurement. MSCs CM were prepared and entrapp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
(32 reference statements)
0
19
0
Order By: Relevance
“…Ingestion of pathogens and disruption of normal microbiota cause enteric infections [ 1 , 2 ]. Enteric infections mainly manifest as fairly distinct clinical syndromes, including acute vomiting, acute watery diarrhea, profuse watery diarrhea, invasive or bloody diarrhea (dysentery), persistent diarrhea, and enteric fever [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ingestion of pathogens and disruption of normal microbiota cause enteric infections [ 1 , 2 ]. Enteric infections mainly manifest as fairly distinct clinical syndromes, including acute vomiting, acute watery diarrhea, profuse watery diarrhea, invasive or bloody diarrhea (dysentery), persistent diarrhea, and enteric fever [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there is a consensus that antibiotics overuse contributed to increased drug resistance and the resulting dysbiosis [ 2 ]. Novel antibiotics are massively produced, but the continuous fear of the resulting antibiotic resistance and dysbiosis elicited researchers to concentrate on the application of nonantibiotic compounds as antimicrobial agents [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro and in vivo studies also reported that secreted products found in MSC-conditioned medium have a wide range of anti-microbial activity, including against E. coli and S. aureus [ 76 , 93 ], E. epidemidis [ 93 ], Vibrio cholerae [ 17 , 94 ], P . aeruginosa [ 95 ], Mycobacterium tuberculosis [ 96 ], Acinetobacter baumannii [ 97 ], and several Candida species [ 98 , 99 ], including effects against biofilm formation [ 100 , 101 ].…”
Section: Msc: Nomenclature Properties Heterogeneity and Realitymentioning
confidence: 99%
“…In addition, recent studies highlight the interest in improving antimicrobial effect by combining of MSC secretome-derived products with nanoparticles. Thus, for example, research has shown the synergic effect of MSC-conditioned media coupled with chitosan nanoparticles against multidrug-resistant Vibrio cholerae [ 94 ]. On the other hand, MSC can produce a direct antiviral effect by secreting antibacterial peptides and proteins (IDO, IL-17, etc.)…”
Section: New Horizons For Clinical Applications Of Mscmentioning
confidence: 99%
“…149,150 Loading of hEVs with a miRNA miR-21 mimic allowed delivery of the miRNA to target cells to improve Wnt/β-catenin controlled migration of keratinocytes in vitro and wound healing in vivo using a diabetic rat model. 151 The secretome of MSC cultures exerts antimicrobial and antibiofilm activity against both Gram-positive and -negative bacterial species, including S. aureus and P. aeruginosa [152][153][154][155] (for a review of MSC antimicrobial peptides see Alcayaga-Miranda et al 94 ). Impregnating wound dressings with a combination of silver nanoparticles and MSC derived hEV increased wound closure, angiogenesis and alpha smooth muscle actin presence in an murine wound model, while also showing in vivo and in vitro activity against P. aeruginosa and broad in vitro antimicrobial activity against E. coli, S. aureus and Candida albicans.…”
Section: Utilizing the Antimicrobial Properties Of Both Bevs And Hevs In Controlling Chronic Wound Microbial Populationsmentioning
confidence: 99%